Menakar program literasi informasi melalui karya ilmiah mahasiswa - Alfida Alfida (Pusat Perpustakaan UIN Syarif Hidayatullah Jakarta, 2015)
The speed and efficiency to obtain information is highly valued by information seekers. Students learn well when the desired information can be found, evaluated and used. using the descriptive quantitative approach on two variables bibliographic analysis and information literacy skills , this study aims to gain an overview of the extent to which students S1 UIN Jakarta FAH using scientific resources in completing college assignments; to analyze barriers experienced in accessing and using sources scientific information , and to determine the appropriate information literacy strategies to be implemented . The results of the study on bibliographic analysis shows that the students use more books than any other resources, more printed materials in Indonesian language, and more resources under two years between 2000 and betwen 2006 to 2010. While the information literacy skills , students scored 49.7 % . Strategies undertaken to refer to Bloom's Taxonomy. This study concludes that the students’ information literacy skills need to be built and improved regularly using different strategies of information literacy programs.